Rethinking Moral Ambiguity in the Qur’an: A Descriptive–Interpretive Meta-Ethical Analysis - Fakhri Afif; Abdul Rouf (International Journal of Islamic Khazanah, 2025)
This article, Rethinking Moral Ambiguity in the Qur’an: A Descriptive–Interpretive Meta-Ethical Analysis, examines how the Qur’an constructs moral value and moral knowledge in ways that generate, rather than eliminate, ethical ambiguity. The study aims (1) to explore the ontological status of moral value in the Qur’an, (2) to analyse the epistemic relationship between reason and revelation in Qur’anic ethics, and (3) to conceptualise moral ambiguity as a hermeneutical resource for ethical deliberation. Methodologically, this research is library-based and employs a descriptive–interpretive reading of selected Qur’anic verses related to key ethical concepts such as khayr, birr, maʿrūf, ʿaql, and shukr, combined with an analytical–comparative dialogue with classical and contemporary Islamic ethical thought and meta-ethical debates on divine command theory and moral realism. The analysis shows, first, that the Qur’an affirms an objective and purposive moral order while simultaneously grounding it in divine will and teleology. Second, the Qur’an attributes a significant epistemic role to human reason and moral intuition, yet subjects them to continuous correction and guidance by revelation. Third, the Qur’an deliberately maintains moral tensions and antinomies, which function as an apparatus for moral transformation rather than a defect to be theologically resolved. The article, therefore, proposes a meta-ethical framework that understands Qur’anic moral ambiguity as intrinsic to scriptural ethics and argues that preserving rather than suppressing this ambiguity opens a productive space for contemporary Islamic ethical reasoning.